IMF Survey, Volume 32, Issue 13. (IMF Survey; IMF Survey ;, 2003)
IMF Managing Director Horst Kohler traveled to Ethiopia on July 5 to discuss the challenges facing the drought-stricken country and to emphasize the IMF's strong commitment to support the country's long-term vision for economic growth and poverty reduction. In subsequent stops on the week-long trip, Kohler visited Kenya, Madagascar, and Mozambique, where he attended the African Union Heads of State meeting in Maputo.